Synthesis of 1-(phenylsulphonyl)-3,5-diarylpyrazoles/ 1-(3-chlorophenyl)-3,5-diarylpyrazoles - D.V. THAKARE, MS.; JAMODE, V.S. (Asian Journal of Chemistry, 2010)
New 1-(phenylsulphonyl)-3,5--diarylpyrazoles (4) have been synthesised by the action of benzene sulphonyl hydrazide with 1,3-diaryl-propan- 1,3-diones (3) in DMF solvent. New 1-(3-chlorophenyl)-3,5-diarylpyrazoles (5) have been synthesised by the action of 3-cblorophenyl hydrazide hydrochloride with 1,3-diaryl-propane-1,3-diones (3) in pyridine solvent.